1989
DOI: 10.1007/bf02535156
|View full text |Cite
|
Sign up to set email alerts
|

The precursors of fecapentaenes: Purification and properties of a novel plasmalogen

Abstract: Fecapentaene-12 and fecapentaene-14 are genotoxic poly-unsaturated ether-lipids produced by the colonic microflora in humans and pigs. Although the fecapentaenes have been extensively characterized, little is known about the nature of the precursors from which they are produced. We purified one form of these precursors from feces of an individual who excreted high levels of fecapentaene-12 and its precursors. Purification was carried out by a series of extractions and precipitation in organic solvents followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As described in a preliminary report (75), we observed that the precursors had the same UV absorbance characteristics as the fecapentaenes, contain alkyl or ester groups-as opposed to hydroxyl groups-covalently linked to the sn-2 and sn-3 positions of the glycerol backbone, and behave like phospholipids, with both polar and nonpolar character. In a recent report (76) we described the methods for isolation and purification of a major form of precursor from feces using a series of extractions with organic solvents, precipitation with acetone, and fractionation by silica and amine HPLC. In addition, we characterized the purified precursor as to its chromatographic properties by comparison to fecapentaene 12 and a synthetic model ether phospholipid.…”
Section: Isolation and Structure Determination Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in a preliminary report (75), we observed that the precursors had the same UV absorbance characteristics as the fecapentaenes, contain alkyl or ester groups-as opposed to hydroxyl groups-covalently linked to the sn-2 and sn-3 positions of the glycerol backbone, and behave like phospholipids, with both polar and nonpolar character. In a recent report (76) we described the methods for isolation and purification of a major form of precursor from feces using a series of extractions with organic solvents, precipitation with acetone, and fractionation by silica and amine HPLC. In addition, we characterized the purified precursor as to its chromatographic properties by comparison to fecapentaene 12 and a synthetic model ether phospholipid.…”
Section: Isolation and Structure Determination Ofmentioning
confidence: 99%
“…The purified precursor was converted to fecapentaene 12 when incubated with whole cells or purified membranes of certain Bacteroides species. Using micellar enzymological techniques, we used commercial lipolytic enzymes to model probable conditions within the human colon (76). Using a combination of standard techniques for producing liposomes and the anaerobic techniques required for handling oxygen-labile polyenyl compounds, we incorporated purified precursor into artificial membranes.…”
Section: Isolation and Structure Determination Ofmentioning
confidence: 99%
“…originate from bacterial modification of polyunsaturated ether phospholipids (5)(6)(7)(8)(9)(10)(11)(12). Synthetic fecapentaene-12 (FP-12*) appears to be highly mutagenic to several strains of Salmonella typhimurium (13)(14)(15) and various genotoxic effects have been observed in murine and mammalian cell types, comprising sister chromatid exchanges (16), mutations at the hypoxanthineguanosine phosphoribosyl transferase locus (16), unscheduled DNA synthesis (17) and DNA single-strand breaks (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been demonstrated that dietary habits may influence fecal mutagenicity to 5a/monc//a TA 100 at the same conditions as fecapentaene mutagenicity is expressed (59,62,63,79,80,151). And finally, the diet has been proposed to provide fecapentaene-precursors (114,115). Even if fecapentaenes do not originate from dietary factors, dietary habits may still be of influence, for instance by affecting the composition of the anaerobic microbial flora in the bowel, and thereby fecapentaene-synthesizing conditions.…”
Section: Epidemiological Aspects Of Fecapentaene Excretionmentioning
confidence: 99%
“…More recently, a phospholipid has been purified and characterized as fecapentaene precursor. Hydrolysis of the so called plasmalopentaenes by phospholipase C and lipase was shown to result in the generation of FP-12 or FP-14 (114). The ultimate origin of the fecapentaenes can be either the diet or cell membranes of the colonic bacterial flora and human colon itself (115).…”
mentioning
confidence: 99%